Design Improvement On The Brake Clearance Adjustment Of Sino-Truck - Henock Ayele (My University, 2016)
Braking System Is One Of The Very Important Active Safety System Which Helps In Avoiding Collisions Of Vehicles. Owing To Its Importance In Avoiding Collisions, It Is Time To Time Performance Improvement Is An Utmost Necessity. It Is Observed That Sino Trucks Are Meeting Collisions Frequently. Lower Performing Brake System Or Brake Out Of Adjustment Is One Of The Reasons Behind Such Collisions, So In This Thesis An Attempt Is Made To Improve The Brake System Of Sino Truck By Altering The Design Of The Slack Adjustment Mechanism. In This Project, I Have Developed A New Model Of An Automatic Slack Adjuster Body For The Brake System Of Sino Truck. The Model Developed Here Uses A Fluid As A Media Of The Slack Adjustment System. The Model Was Corroborated With The Measurement Data Collected From The Truck Foundation Brake Components I.E. The Area Of The Brake Chamber, The Input Pressure Of The Chamber, The Length Of The Push Rod, The Original Pad Thickness And The Arm Span Of The Slack Adjuster Using Cad And Analysis Software Ansys. Numerical Results Obtained Are Compared With The Literature And Found Acceptable.